Are Pharmaceutical Companies Ready to Distribute Vaccines and Medical Supplies in the Event of a New Pandemic? An Investigation into the Intricacies Between Intellectual Property Rights v. Human Rights - Pandey, Saugat Jung; Khanal, Srijan (Kathmandu School of Law Review, 2025)
This paper will delve into the critical intersection of business interests and human rights, particularly focusing on the role of pharmaceutical companies in ensuring equitable access to essential medical supplies and vaccines during pandemic and other public health emergencies whilst also retaining these companies Intellectual Property Rights. The paper will look into the UN Guiding Principles on Business and Human Rights, emphasizing on the obligation of business enterprises such as pharmaceutical companies to facilitate in accessible and affordable medical supplies, especially for low-income countries. This paper will analyze how pharmaceutical companies have fulfilled their human rights obligations during the public health emergency of international concern like the COVID-19 while also upholding their intellectual property rights, highlighting both the shortcomings and successes. Also considering lessons learned from the recent pandemic, the paper will also propose strategies to strike a balance between business interests and human rights. This article aims at contributing to the ongoing discourse surrounding business and human rights by offering recommendations that can guide the actions of business enterprises in promoting equitable access to essential medical supplies in times of public health crisis in future.